Comparison of indoor air quality between building type in campus buildings - Erlandson, Grant, author; Schaeffer, Joshua, advisor; Carter, Ellison, committee member; Magzamen, Sheryl, committee member; Reynolds, Stephen, committee member (Colorado State University. Libraries, 2018)
The average American spends an estimated 90% of their time indoors on any given day. Rapid urbanization is also sweeping the country leading to ever increasing time spent in the built environment. Human exposure to the surrounding environment accounts for 90% of all disease. The air we breathe represents a major component of that exposure and becomes increasingly relevant as more time is spent indoors. Many studies have set out to characterize and improve indoor air quality in various settings from the workplace to schools. However, few have investigated higher education and its shift toward green, sustainable buildings. The objective of this research was to evaluate the effects of building type and occupancy on indoor air quality in higher education buildings. We measured LEED certified, retrofitted, and conventional building types on a college campus for particulate matter, formaldehyde, carbon dioxide, and nitrogen oxides. For each building type, we conducted multi-zonal, 48 hour measurements during times when the buildings were occupied and unoccupied. Statistically significant differences in two size fractions of particulate matter were observed between building types. Carbon dioxide and particulate matter concentrations were significantly higher during occupied sampling when compared to unoccupied. Results from this study suggest that occupancy status has a larger impact on indoor air quality in campus buildings than building type.